APPLICATION OF MUROTTAL METHOD IN IMPROVING THE ABILITY TO MEMORIZE SHORT SURAHS IN RA PERWINDA 4 MADINING SOPPENG - Ernawati; Maswati; Jafar Kalbi (PT. Jurnal Center Indonesia Publisher, 2025)
The type of research used is class action research. Data collection techniques used are observation, documentation, tests. Data analysis techniques used are data collection, data reduction, data presentation, and conclusion. It can be concluded that the application of murottal method in RA Perwinda 4 Madining, Soppeng, proved effective in improving the ability to read and memorize the Qur'an children through an interactive and fun approach. The use of murottal audio from famous reciters/qariahs helps the child hear and imitate the correct recitation as per Tajweed, while the combination with creative methods like hand gestures and hijaiyah card games keeps their engagement. The study showed a significant increase in the ability to memorize short Surahs, from an average of 21.9% in the pre-cycle to 85.9% in the second cycle. This approach also supports the natural formation of Islamic character, making the murottal method an effective and innovative strategy in learning the Qur'an at an early age.